Answer:
-2 (6x - y) = -12x + 2y
Step-by-step explanation:
By using the distributive property, you start by multiplying -2 and 6x which gets you -12x. You then multiply -2 and -y (in other words -y = -1y) so, -2* -y would get you 2 as a negative multiplied by a negative is a positive. So, adding them together would get your final answer: -2 (6x - y) = -12x + 2y
The answer is d 41 X 12= 492
Step-by-step explanation:
12 (12 + 17)
12(41)
= 492
Answer:
10 bracelets
Step-by-step explanation:
we need to convert 5 ft to inches
1 ft = 12 inches
multiply by 5
5 ft = 60 inches
60 inches of yarn, 6 inches per bracelet
60/6 = 10
10 bracelets
The answer is 2
------------------------